2020
DOI: 10.3390/ijms21124506
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophagy—Implications for Microautophagy and Health

Abstract: Nucleophagy, the selective subtype of autophagy that targets nuclear material for autophagic degradation, was not only shown to be a model system for the study of selective macroautophagy, but also for elucidating the role of the core autophagic machinery within microautophagy. Nucleophagy also emerged as a system associated with a variety of disease conditions including cancer, neurodegeneration and ageing. Nucleophagic processes are part of natural cell development, but also act as a response to various stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Mammalian cells have a nuclear lamina structure, which is different from that of lower eukaryotes, such as yeasts, with no comparable lamins or a fibrous nuclear envelope scaffold ( 29 ). Nevertheless, nucleophagy is considered to play an important role in maintaining cellular genomic stability, detecting DNA damage, and regulating cellular apoptosis, as well as cellular senescence ( 30 , 31 ). MN assays showed increased MN frequencies in breast cancer lymphocytes, which were correlated with the progression of breast cancer ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian cells have a nuclear lamina structure, which is different from that of lower eukaryotes, such as yeasts, with no comparable lamins or a fibrous nuclear envelope scaffold ( 29 ). Nevertheless, nucleophagy is considered to play an important role in maintaining cellular genomic stability, detecting DNA damage, and regulating cellular apoptosis, as well as cellular senescence ( 30 , 31 ). MN assays showed increased MN frequencies in breast cancer lymphocytes, which were correlated with the progression of breast cancer ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian cells have a nuclear lamina structure, which is different from that of lower eukaryotes, such as yeasts, with no comparable lamins or a brous nuclear envelope scaffold [23]. Nevertheless, nucleophagy is considered to play an important role in maintaining cellular genomic stability, detecting DNA damage, and regulating cellular apoptosis, as well as cellular senescence [24,25]. MN assays showed increased MN frequencies in breast cancer lymphocytes, which were correlated with the progression of breast cancer [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear autophagy, a new type of selective autophagy, is responsible for selectively removing damaged or unnecessary nuclear substances in cells (Fu et al, 2018). Nuclear autophagy happens in a variety of conditions, including starvation, rapamycin-induced TORC1 inactivation, nuclear vacuolar junction (NVJ) expansion, and nuclear fibrillary lamina defects (Bo Otto and Thumm, 2020). In 2009, it was first reported that LMNA/C is involved in the development of mammalian nuclear autophagy.…”
Section: Prospectionmentioning
confidence: 99%